2013
DOI: 10.1002/apj.1721
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Cd(II) from its aqueous solution using environmentally benign vegetable oil as liquid membrane

Abstract: This work is intended for extraction and recovery of toxic heavy metal components, viz. Cadmium (Cd), from the industrial wastewater using liquid membrane (LM)-based separation technique. Exploring environmental benignity in the solvent (LM) is the main aim of this work. Vegetable oils are potential candidates toward that. Presence of carrier component in solvent often augments the solute transport mechanism. Although N,N-dimethyloctylamine (DMOA) is a very good carrier to show excellent extraction, the recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…From our previous studies of BLM 1 and SLM 2 configurations, we reported that Na 2 -EDTA is an efficient stripping agent for the stripping of M from the membrane phase due to its metal chelating capacity. From our previous studies of BLM 1 and SLM 2 configurations, we reported that Na 2 -EDTA is an efficient stripping agent for the stripping of M from the membrane phase due to its metal chelating capacity.…”
Section: Solute Transport Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…From our previous studies of BLM 1 and SLM 2 configurations, we reported that Na 2 -EDTA is an efficient stripping agent for the stripping of M from the membrane phase due to its metal chelating capacity. From our previous studies of BLM 1 and SLM 2 configurations, we reported that Na 2 -EDTA is an efficient stripping agent for the stripping of M from the membrane phase due to its metal chelating capacity.…”
Section: Solute Transport Methodologymentioning
confidence: 99%
“…1 Industries such as pulp and paper, battery, fertilizer, chlor-alkali, alloy and steel, paints and pigments, petrochemicals and mining activities include the major source of these toxics. cadmium and lead which cause serious damage to the environment and the human health in particular.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contamination of aqueous environment by hazardous heavy metals such as lead(II) and cadmium(II), through industrial effluents, is a major problem and an universal concern to the research community owing to their carcinogenic, highly toxic and non-biodegradable nature [1,2]. Attention has been paid to reduce the concentrations of lead (II) and cadmium (II) in the effluents to their permissible limits (0.10 ppm for lead(II) and 0.03 ppm for cadmium(II)) set by the World Health Organization (WHO) [3].…”
Section: Introductionmentioning
confidence: 99%
“…The main benefits of selecting coconut oil are its low cost, easy availability and bio degradability. Moreover, it has high viscosity, high boiling point and high chemical stability in membrane pores [1,2,[16][17][18][19]. Various parameters such as concentration of feed phase, pH, concentration of carrier in membrane phase, concentration of stripping agent have also been studied.…”
Section: Introductionmentioning
confidence: 99%